Factors contributing to and biological concepts about early pregnancy among Filipino adolescent mothers - Jastine Jane R. Ballon; Joseline R Tamoria (Intelektual Pustaka Media Utama, 2023)
In the 21st century society, teenage life is the most deceitful stage in the life of a person. This is where teenagers adjust their physical and emotional changes in life. Early pregnancy becomes a social problem in our society and also in the Philippines. The study sought to determine the factors contributing to and biological concepts of adolescent mothers in early pregnancy. This mixed-method research purposively involved 30 adolescent mothers who enrolled in a state university in Zambales, Philippines. Results revealed that most adolescent mothers gave birth when they were 17-19 years old; most of them continue their studies and returned to school after three years and above. Among the factors, family and mass media do not affect their engagement in early pregnancy. Filipino adolescent mothers are all aware of the biological concepts in terms of the types of fertility control, biological processes, signs of pregnancy, and in the effects of early pregnancy. Five themes emerged on how young moms overcome their teenage pregnancy experiences. The respondents are all aware of the biological concepts in early pregnancy. Gender and development office of the university may craft programs that empower student-teenagers to cope with the challenges that they face during pregnancy.